Pengaruh Suhu dan Ketebalan Irisan Terhadap Kerupuk Otak-Otak Ikan Menggunakan Teknologi Vacuum Frying - Salma Hairunisa; Tamrin Tamrin; Yuni Safitri; Sandi Asmara (Jurnal Agricultural Biosystem Engineering, 2026)
Lampung Province is known for its enormous potential for marine and fishery resources in Indonesia. This condition will support the supply of fish for making otak-otak. Vacuum frying otak-otak can increase its shelf life, so otak-otak products have the potential for export. This study aims to analysis the effect of temperature and slice thickness in vacuum frying on the quality characteristics of fish otak-otak chips. Frying temperature and differences in slice thickness affect the quality characteristics of fish otak-otak chips, especially on the parameters of yield, colour, and crispiness, but do not significantly affect water content, taste, and aroma. Treatment with longitudinal slices divided into 3 tends to produce a crispier texture and a higher level of acceptance than whole otak-otak. The combination of 85 °C temperature with longitudinal slices resulted in the fastest frying time, namely 85 minutes, with the lowest water content of 4.0%. In contrast, the treatment of 75 °C temperature with whole slices resulted in the longest frying time, namely 139 minutes, with the highest water content of otak-otak fish at 4.7%. The best colour quality was obtained at a temperature of 75˚C with longitudinal slices with a score of 3.78, while the highest level of crispiness was obtained at a temperature of 85 °C with longitudinal slices with a score of 4.25 (crispy).